C‐Reactive Protein Level and the Incidence of Eligibility for Statin Therapy: The Multi‐Ethnic Study of Atherosclerosis - Mann, Devin M. (Wiley Periodicals, Inc., 2012)
BACKGROUND: Given the results of the Justification for the Use of Statins in Primary Prevention: An Intervention Trial Evaluating Rosuvastatin (JUPITER) trial, statin initiation may be considered for individuals with elevated high‐sensitivity C‐reactive protein (hsCRP). However, if followed prospectively, many individuals with elevated CRP may become statin eligible, limiting the impact of elevated CRP as a treatment indication. This analysis estimates the proportion of people with elevated CRP that become statin eligible over time. HYPOTHESIS: Most people with elevated CRP become statin eligible over a short period of time. METHODS: We followed 2153 Multi‐Ethnic Study of Atherosclerosis (MESA) participants free of cardiovascular disease and diabetes with low‐density lipoprotein cholesterol <130 mg/dL at baseline to determine the proportion who become eligible for statins over 4.5 years. The proportion eligible for statin therapy, defined by the National Cholesterol Education Program (NCEP) 2004 updated guidelines, was calculated at baseline and during follow‐up stratified by baseline CRP level (≥2 mg/L). RESULTS: At baseline, 47% of the 2153 participants had elevated CRP. Among participants with elevated CRP, 29% met NCEP criteria for statins, compared with 28% without elevated CRP at baseline. By 1.5 years later, 26% and 22% (P = 0.09) of those with and without elevated CRP at baseline reached NCEP low‐density lipoprotein cholesterol criteria and/or had started statins, respectively. These increased to 42% and 39% (P = 0.24) at 3 years and 59% and 52% (P = 0.01) at 4.5 years following baseline. CONCLUSIONS: A substantial proportion of those with elevated CRP did not achieve NCEP‐based statin eligibility over 4.5 years of follow‐up. These findings suggest that many patients with elevated CRP may not receive the benefits of statins if CRP is not incorporated into the NCEP screening strategy. Additional Supporting Information may be found in the online version of this article. The Multi‐Ethnic Study of Atherosclerosis (MESA) was supported by contracts NO1‐HC‐95159 through NO1‐HC‐95165 and NO1‐HC‐95169 from the National Heart, Lung, and Blood Institute. This research was also supported by grant 1K23DK081665, a Patient‐Oriented Mentored Scientist Award through the National Institute of Diabetes, Digestive, and Kidney Diseases (to DMM). The authors have no other funding, financial relationships, or conflicts of interest to disclose.